The Physical Activity-Dependent Hematological and Biochemical Changes in School Horses in Comparison to Blood Profiles in Endurance and Race Horses - Małgorzata Maśko; Małgorzata Domino; Tomasz Jasiński; Olga Witkowska-Piłaszewicz (Animals, 2021)
Blood testing is one of the most important ways to improve performance, facilitate recovery and monitor the training of endurance and race horses. However, little is known about the physical activity-dependent changes of blood parameters in horses used for pleasure and in riding schools. This study aimed to perform routine blood tests for training monitoring of sport horses in three different horse types of use. Then the values of blood indicators were compared between school, endurance and race horses to find similarities in the physical activity-dependent profile. The study was carried out on 15 endurance, 15 race and 15 school healthy horses who underwent the typical effort for their disciplines. The hemogram parameters, creatine phosphokinase (CPK), aspartate aminotransferase (AST), blood lactate (LAC), and total serum protein (TSP) concentrations were measured using the same protocol and equipment. Measurements of main hematological and biochemical physical activity-dependent parameters were conducted before, immediately after and 30 min after training. In school horses, the physical activity-dependent increase of WBC (40.9%) and CPK (76.4%) was similar to endurance horses, whereas an increase of RBC (19.1%), HGB (18.6%) and HCT (19.4%) were more similar to race horses. The moderate effort-dependent increase of LAC concentration (2775%) was lower than in race horses (7526%) and higher than in endurance horses (390%). Limiting the training or work monitoring assessment of school horses to only the endurance or racing blood profile may result in the omission of significant changes in hematological and biochemical parameters.